2020
DOI: 10.1213/ane.0000000000005002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High-Flow Nasal Oxygen on Carbon Dioxide Accumulation in Apneic or Spontaneously Breathing Adults During Airway Surgery: A Randomized-Controlled Trial

Abstract: BACKGROUND: High-flow nasal oxygen (HFNO) is an emerging technology that has generated interest in tubeless anesthesia for airway surgery. HFNO has been shown to maintain oxygenation and CO2 clearance in spontaneously breathing patients and is an effective approach to apneic oxygenation. Although it has been suggested that HFNO can enhance CO2 clearance during apnea, this has not been established. The true extent of CO2 accumulation and resulting acidosis using HFNO during prolonged tubeless anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…[40][41] However, studies recently published by Piosik ZM et al and Booth AWG et al indicates that although the apneic oxygenation of HFNO can ensure the oxygenation of patients and maintain long-term tubeless anesthesia, it is easy to result in CO2 accumulation and respiratory acidosis when the apnoea time is greater than 30 minutes. [32,42] This extends previous knowledge and has implications for the safe application of HFNO during prolonged procedures.…”
Section: Discussionsupporting
confidence: 75%
“…[40][41] However, studies recently published by Piosik ZM et al and Booth AWG et al indicates that although the apneic oxygenation of HFNO can ensure the oxygenation of patients and maintain long-term tubeless anesthesia, it is easy to result in CO2 accumulation and respiratory acidosis when the apnoea time is greater than 30 minutes. [32,42] This extends previous knowledge and has implications for the safe application of HFNO during prolonged procedures.…”
Section: Discussionsupporting
confidence: 75%
“…Taking advantage of the fact that HFNO can significantly prolong the safe apnoea time, many medical institutions have successfully carried out tubeless anesthesia, especially in short operations with shared airway such as subglottic stenosis and upper airway surgeries [ 33 , 34 ]. However, studies recently published indicates that although the apneic oxygenation of HFNO can ensure the oxygenation of patients and maintain long-term tubeless anesthesia, it is easy to result in CO 2 accumulation and respiratory acidosis when the apnoea time is greater than 30 min [ 35 , 36 ]. This extends previous knowledge and has implications for the safe application of HFNO during prolonged procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has recently been shown that CO 2 accumulation in adults under general anesthesia using HFNO during apnea was more than double that of spontaneous breathing. 14 In addition, in our case, postinterventional FHR monitoring reassuringly showed normal values; however, adhering to only minimum standards of FHR monitoring (as outlined by the American College of Obstetricians and Gynecologists [ACOG] Committee Opinion 2019 15 ) ultimately limits conclusions about fetal safety during the procedure. Further studies, including the incorporation of arterial blood gases, supplemented by continuous FHR monitoring, are needed to compare these 2 strategies in parturients.…”
Section: Discussionmentioning
confidence: 63%